2021
DOI: 10.3389/fgene.2021.721252
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Gene Signature Impacts the Immune Infiltration and Predicts the Prognosis of Kidney Renal Clear Cell Carcinoma

Abstract: Background: Oxidative stress is related to oncogenic transformation in kidney renal clear cell carcinoma (KIRC). We intended to identify a prognostic antioxidant gene signature and investigate its relationship with immune infiltration in KIRC.Methods: With the support of The Cancer Genome Atlas (TCGA) database, we researched the gene expression and clinical data of KIRC patients. Antioxidant related genes with significant differences in expression between KIRC and normal samples were then identified. Through u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…found that GSTM2 could inhibit oxidative stress-induced renal cell apoptosis and inflammation in anti-glomerular basement membrane antibody-induced glomerulonephritis ( 59 ). Ren and his colleagues also found that GSTM3, as an antioxidant gene signature, to regulate immune cell infiltration and to predict the prognosis in patients with kidney renal clear cell carcinoma ( 60 ). Low expression of GSTM2/4 decrease ROS metabolism to induce Immunologic dysfunction in type 1 diabetes ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…found that GSTM2 could inhibit oxidative stress-induced renal cell apoptosis and inflammation in anti-glomerular basement membrane antibody-induced glomerulonephritis ( 59 ). Ren and his colleagues also found that GSTM3, as an antioxidant gene signature, to regulate immune cell infiltration and to predict the prognosis in patients with kidney renal clear cell carcinoma ( 60 ). Low expression of GSTM2/4 decrease ROS metabolism to induce Immunologic dysfunction in type 1 diabetes ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant-related genes may be related to tumorigenesis as they play a major role in regulating oxidative stress and protecting against ROS [ 17 ]. Studying the relationship between antioxidant genes and tumorigenesis may facilitate the discovery of novel targets for predicated prognosis and treatment [ 18 ]. However, the prognostic values of antioxidant-related genes and their biological functions in sarcomas remain rudimentary and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…After referring to the literature, we finally selected 4 prognostic-related risk models, namely, 9-gene signature (Zhong) ( 38 ), 7-gene signature (Jiang) ( 39 ), 7-gene signature (Chen) ( 40 ), and 6-gene signature (Ren) ( 41 ), for comparing the prediction performance with our 8-gene model. To make the model comparable, we calculated the riskscore of each KIRC sample in the TCGA using the same method based on the corresponding genes in the 4 models.…”
Section: Resultsmentioning
confidence: 99%